The Ark of Nuh - Khan ,Saniyasnain (Goodword books, 2024)
This board book tells the story of Prophet Nuh (AS) in a way that is simple and engaging for young children. It shares his strong faith, patience, and efforts to guide people towards Allah$1 (Bs message, while also teaching values like trust in Allah, perseverance, and compassion for all living creatures. The story is supported by bright, colorful illustrations that capture children$1 (Bs attention and imagination. With its sturdy design, the book is perfect for toddlers and preschoolers, helping families nurture early spiritual learning and bonding.s
This beautifully illustrated board book introduces young readers to the story of Prophet Nuh (AS). Told in simple, engaging language, it highlights his faith, patience, and dedication in spreading Allah$1 (Bs message. The book emphasizes values such as trust in Allah, perseverance, and compassion for all creatures, while vibrant illustrations bring the story to life. The durable board book format makes it perfect for toddlers and preschoolers, encouraging repeated reading, family bonding, and early spiritual growth.s
This enchantingly illustrated board book introduces children to the inspiring story of Prophet Nuh (AS). Through simple and engaging language, young readers learn about his unwavering faith, patience, and dedication in spreading Allah$1 (Bs message. The story emphasizes values such as perseverance, trust in Allah, and compassion for all creatures, making it both educational and spiritually nurturing.s
Children under 5 years of age Parents and educators introducing Quranic stories to little learners Families seeking to instill Islamic values from an early age